Speech Act Analysis of the Song Lyric Don’t Smile by Sabrina Carpenter - Yuliani Milantina; Adip Arifin; Syamsuddin Rois (English Language Education Department, Universitas Majalengka, 2025)
This study analyzes the lyrics of Don’t Smile by Sabrina Carpenter using John Searle’s speech act theory to uncover the emotional and communicative layers within the lyrics. This theory classifies utterances into five types: assertives, directives, expressives, commissives, and declaratives. The findings of the study reveal that expressive speech acts dominate the lyrics, followed by assertive and directive acts. Commissive speech acts appear less frequently, and no declarative acts were identified. The song reflects the speaker’s emotional struggle, emphasizing raw emotional expression and the process of healing through art. This research highlights how speech act theory can provide deeper insights into the use of language in song lyrics, transforming music from mere entertainment into a powerful medium for emotional expression that resonates deeply with its listeners.